Penilaian Kerusakan Tanah Pada Produksi Biomassa Perkebunan Di Kecamatan Kuala Cenaku Kabupaten Indragiri Hulu - Candra Richardo Saragih; Besri Nasrul; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to identify the damage of the soil as well as evaluating the extent of soils damage due to the production of biomass plantations. This research was conducted using survey methods. The result shows that based on evaluation on plantation of biomass production which is as a result of forest conversion, founded there are same soil chemical and  physical are changing. The physical soil changes on plantation area are moisture content that  increasing 1.2%, decrease of water content 18.1% on sub group haplosaprists soil, increaseing of weight 0,19 g/cm3 on sub group endoaquents land, decrease of weight to 0.02 g/cm3 on haplosaprists soil sub group, the increase in the value of specific gravity 0.36 g/cm3 soil sub group on endoaquents heavy type of value, decrease ofland sub group haplosaprists 0.27 g/cm3, the decline in the value of the total pore space is 1.65 % on the land sub group endoaquents and 2.1 % on the land sub group haplosaprists. Chemical changes on plantations are decreasing of pH soils 2.1 on the sub group haplosaprists land, a decrease of DHL value 1.79 dS/m on the sub group endoaquents land, an increase of 0.36 dS/m on the sub group haplosaprists land,  redox value of soil on the 25.5 mV on the sub group haplosaprists land. Biological properties of the soil changes on the plantation include the increasing amount of soil microbes 2.6 cfu/g on the sub group endoaquents soil and 2.1 cfu/g on sub group at haplosaprists soil.